The plant half products for fortification of foodstuffs - Simahina, Galina; Naumenko, Nataliia (My University, 2023)
The subjects for researching are the green parts (tops) of beets, ramsons, nettle, garlic, pea husk, and onion skin. We confirmed the high content of indispensable amino acids – 87 to 283 mg per 100 g of leucine; 72 to 205 mg per 100 g of lysine; 504 to 1375 mg per 100 g in total. Dispensable amino acids in maximal amount are represented by glycine (83 to 377 mg per 100 g), alanine (87 to 251 mg per 100 g). Proteins in researched materials are outstanding with high grade of proteolysis (28.61 % for garlic; 28.81 % for nettle; 29.37 % for sugar beet), which slightly differs from the control index (milk proteins, 30.01 %). Taking green mass for a base to create the biologically active additives and polyfunctional ingredients is grounded scientifically, expedient technologically, and profitable economically. We have recommended using the green mass of plants for enrichment of any food bases in production of foodstuffs for both domestic and foreign markets.
Keywords: functional properties; fortified foods; biologically active components; функціональні властивості; збагачені продукти харчування; біологічно активні компоненти; кафедра гуманітарних дисциплін; кафедра технології оздоровчих продуктів